Indoor Staying During Winter Season Makes People More Susceptible to Flu - Acharya, B; Thapa, K (Journal of Nepal Health Research Council, 2016)
An infectious diseases caused by RNA virus, the influenza is also commonly known as Flu. It mainly transmitted through air by coughs or sneezes of infected. The symptoms of flu like fever and headache are the result of the huge amounts of proinflammatory cytokines and chemokinesÂ (such asÂ interferon orÂ tumor necrosis factor) produced from influenza-infected cells. The activated vitamin has extreme effects on human immunity. Vitamin D prevents too much release of cytokines and chemokines. Staying much time indoor, away from contact of sunlight during winter season lowers the vitamin D level in human body. Thus, the chance of getting flu increases in winter season. Formulation of policy regarding vitamin D supplementation in diet for people such as elderly and with low sunlight exposure is hereby recommended. It will be beneficial to reduce influenza related morbidity and mortality during winter season. Keywords: Flu; influenza; indoor staying; susceptibility; winter season.